Açúcar granulado ou gel no tratamento de feridas em cães - Serafini, Gabriele Maria Callegaro (2012)
Sugar is one of the most widely used products in the treatment of wounds in veterinary medicine. Its main advantage is the hygroscopic effect on tissues and the bacterial death by plasmolysis, making it a bactericidal agent due to the physical effect observed, without leading to bacterial resistance as it might occur with antibiotic therapy. The objective of this experiment was to compare cicatricial evolution in cutaneous wounds with the topical use of sugar both granulated and in the form of a gel. For such, 16 canine wounds were treated, where eight received treatment with granulated sugar (group A) and eight with sugar gel (group G). Evaluations such as mensurations of the wounded areas, bacteriological cultures and observation of the aspect of the lesions were done weekly from the moment of the first examination until the formation of enough granulation tissue to suspend the use of the products. When comparing the decline in the area between groups no statistical difference was observed at any time. However, when the areas were analyzed in each group's interval, it was possible to notice a statistically significant decline between days 1-14 and 7-14 in the group treated with sugar. In the group treated with the gel, beside those intervals, a significant decline was also noticed between days 1-7. In terms of the frequency of negative bacteriological culture, there was no statistical difference between groups, not even in the different moments of each group. The time taken for the granulation tissue to be fully formed varied from 7 to 14 days in both groups. As to applicability, the gel showed better adhesion to the wounds and filling of the product subcutaneously more effectively than the granulated sugar. The conclusion reached is that both the sugar and the gel were effective in healing the animals' wounds in this experiment, the gel having demonstrated precocity in cicatricial retraction in the first seven days.